Increasing Elementary Students’ Reading Literacy through Local Folklore-Based Tutoring - Everhard, Everhard Markiano Solissa; Mustamin, Kaso; Yani, Ahmad; Handayani, Tri; Sapulette, Viona (International Journal of Community Service (IJCS), 2025)
The present study investigates the effectiveness of local folklore-based tutoring activities in enhancing elementary students’ reading literacy skills in Indonesia. Employing a quantitative, quasi-experimental design, the research involved two intact classes of fifth-grade primary school students. The experimental group received literacy tutoring utilizing illustrated local folklore books, while the control group followed the conventional curriculum. Pre- and post-tests were administered to assess development in reading interest and comprehension. Statistical analysis demonstrated a significant difference between the two groups, with the experimental group exhibiting a higher post-test mean (79.74) compared to the control group (68.95), and a gain score of 9.91 versus 1.72, respectively. These findings indicate that integrating local folklore into reading instruction not only increases students' motivation to read but also results in meaningful improvements in literacy outcomes. The results support the adoption of culturally relevant, narrative-based approaches in primary literacy education and underscore the broader role of local wisdom in fostering literacy engagement